(untitled) - Phạm, Thái Hồng (Cần Thơ, 2018)
This thesis introduce about English as a foreign language teachers' perceptions of using powerpoint as an ICT tool for teaching vocabulary in Kien Giang province .
Keywords: English language,Tiếng Anh; Study and teaching,Học và dạy học